Benznidazole treatmentof Chagasic encephalitis in pregnant women with AIDS - Bisio, Margarita María Catalina (2013)
We report a case of chagasic meningoencephalitis reactivation in a pregnant woman co-infected with Trypanosoma cruzi and HIV that was successfully managed with benznidazole and highly active antiretroviral therapy. Early diagnosis enabled rapid specific treatment that improved the health of the patient and her baby.